Regulations on The Distribution of Special Autonomy Funds - Samuel Saflessa; Baharullah Akbar; Irawan Irawan; Petrus Polyando (Lembaga Riset dan Inovasi Al-Matani, 2023)
Twelve years since the enactment of Law Number 21 of 2001 concerning special autonomy for the Province of Papua and specifically the Province of West Papua since 2008 based on Law Number 35 of 2008 (State Gazette of the Republic of Indonesia Number 4151) which has been amended into Law Law Number 35 of 2008 Number 112, Supplement to the State Gazette of the Republic of Indonesia Number 4884, it turns out that it has not been able to prosper the people of West Papua. In fact, with abundant natural resources, Papua should be able to improve the economy and welfare of its people. Since the 2008-2019 period, the provision of special autonomy funds for the Province of West Papua which has reached IDR 30.27 trillion has not made a significant change for the people. With a reality like this, if the government does not take appropriate anticipatory steps to improve the economy and welfare of the people of West Papua, it will greatly open up opportunities for the people of Papua and West Papua to sue the government as a result of the unsuccessful implementation of the special autonomy that has been enforced in the easternmost province of Indonesia.